Hubungan Vitamin D dengan Kejadian Lupus di Rumah Sakit Pendidikan Jakarta - Fajar Maulana; Diana Laila Ramatillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that commonly affects women of reproductive age and is characterized by immune system dysregulation. Vitamin D acts as an immunomodulator that influences disease activity through the regulation of adaptive and innate immune responses. This study aims to analyze the relationship between patient characteristics and vitamin D levels and evaluate changes in levels after supplementation in SLE patients at the Jakarta Teaching Hospital. This study used a descriptive analytical design with a retrospective cross-sectional approach based on medical records of 55 patients from November 2024 to May 2025. The variables analyzed included age, gender, and 25(OH)D levels categorized as deficiency, insufficiency, and normal. The relationship analysis was performed using the Chi-Square test. The results showed that most patients were in the deficiency and insufficiency categories. There was a significant relationship between age and vitamin D levels (p=0.037) and between gender and vitamin D levels (p<0.033). A sub-analysis was also conducted on 7 of 55 patients who received 5,000 IU vitamin D3 supplementation for 30 days. This small group found an increase in 25(OH)D levels to within the normal range without signs of toxicity. It was concluded that vitamin D has potential as an adjuvant therapy in SLE patients.